Hypokalaemic Periodic Paralysis in a Patient with Subclinical Hyperthyroidism: A Rare Case - Hegde, Swati (J Clin Diagn Res, 2016)
Thyrotoxic Periodic Paralysis (TPP) is an uncommon disorder. Though many cases of hypokalaemic periodic paralysis are reported in overt hyperthyroidism, hypokalaemic paralysis in subclinical hyperthyroidism is very rare. Subclinical hyperthyroidism is characterised by circulating TSH levels below reference range and normal thyroid hormone levels. We describe a case of 32-year-old Asian male who presented to the emergency department with acute onset weakness and hypokalaemia with no previous history of thyroid disorder or any signs and symptoms suggestive of hyperthyroidism. He was subsequently diagnosed with Graves’ disease with subclinical hyperthyroidism.